06 KONTRIBUSI PENDAPATAN TENAGA KERJA PEREMPUAN TERHADAP PENDAPATAN KELUARGA (Studi Kasus Pedagang Sayuran di Pasar Sentral Malino Kecamatan Tinggimoncong, Kabupaten Gowa) - Jurnal Agribis; Ferina Afriani; Abd. Asis Pata; Azisah Azisah (Universitas Muslim Maros, 2020)
This research was conducted in Malino Central Market, Tinggimoncong District, Gowa Regency. This location was chosen with the consideration that Malino is the largest vegetable producer in Tinggimoncong District. So that there are many women who sell vegetables lining the Central Malino market. The data used are primary data obtained from direct observations and interviews with the help of a questionnaire list. The purpose of this study was to determine the contribution of income of women vegetable traders in supporting family income in the Central Malino market, and to determine the time spent working for women who sell vegetables. This research uses simple random sampling method. With a population of 112, respondents chose 10%, namely 11 people from the existing number. This research uses descriptive qualitative data analysis method. The results of this study are that the income of women who sell vegetables is greater than that of husbands who are only farmers and the contribution of women traders is 52.88%, while husbands are only 47.12%. This shows that women who sell vegetables have a big contribution to family income. Meanwhile, the average time they spend in the Malino Central market in a day is that women traders take care of the household with an average of 9.00 hours (36.74), selling vegetables an average of 5.36 hours with a percentage (22 35), and doing other activities with an average of 9.82 percentages (40.9).